2000
DOI: 10.1016/s0002-9440(10)64789-x
|View full text |Cite
|
Sign up to set email alerts
|

Substance P (Neurokinin-1) and Neurokinin A (Neurokinin-2) Receptor Gene and Protein Expression in the Healthy and Inflamed Human Intestine

Abstract: Increasing evidence suggests that tachykinins are involved in the control of pathophysiological states, such as inflammation. The precise localization of tachykinin receptors is of paramount importance in the search for their possible physiological and pathological role; in this study, therefore, we attempted to define cellular sites of substance P (NK-1R) and neurokinin A (NK-2R) receptor expression in the healthy and the inflamed human intestine by in situ hybridization and immunohistochemistry. In the norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
139
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(150 citation statements)
references
References 50 publications
(51 reference statements)
7
139
1
Order By: Relevance
“…Under normal conditions, NK-1R expression in colonocytes is low (36), but its expression is increased in colonocytes in IBD patients (36,37) and ileal epithelial cells during C. difficile toxin A-induced experimental enteritis (38). Previous studies also indicated expression of NK-1R in intestinal epithelial cells (4,5).…”
Section: Discussionmentioning
confidence: 98%
“…Under normal conditions, NK-1R expression in colonocytes is low (36), but its expression is increased in colonocytes in IBD patients (36,37) and ileal epithelial cells during C. difficile toxin A-induced experimental enteritis (38). Previous studies also indicated expression of NK-1R in intestinal epithelial cells (4,5).…”
Section: Discussionmentioning
confidence: 98%
“…Several reports have demonstrated the presence of NK1R in different neuronal and non-neuronal cells in the gastrointestinal tract (Sternini et al 1995;Goode et al 2000). In pathological states, such as inflammation in Crohn's disease, NK1R expression is up-regulated (Renzi et al 2000). Various parts of the genitourinary tract, such as the urinary bladder or the kidney, also exhibit neurokinin 1 receptor expression (Meini et al 1994;Chen and Hoover 1995).…”
Section: Oryctolagus Cuniculus Nk2r Sus Scrofa Nk2rmentioning
confidence: 99%
“…SP's primary receptor, the neurokinin-1 receptor (NK-1R), can mediate a variety of physiologic and pathophysiologic responses, including cell proliferation, migration, and inflammation (8). The NK-1R has been identified in epithelial cells in rodent models of colonic inflammation (9,10) and in patients with UC as well as Crohn disease (11)(12)(13)(14). However, not all of these studies are in agreement regarding epithelial NK-1R expression in UC: some studies have shown an increase (12,13), whereas others have not (11,14).…”
mentioning
confidence: 99%
“…The NK-1R has been identified in epithelial cells in rodent models of colonic inflammation (9,10) and in patients with UC as well as Crohn disease (11)(12)(13)(14). However, not all of these studies are in agreement regarding epithelial NK-1R expression in UC: some studies have shown an increase (12,13), whereas others have not (11,14). The NK-1R has been identified in many cancers, including skin, gastrointestinal, laryngeal, pancreatic, ovarian, brain, thyroid, and breast cancers (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%